2008
DOI: 10.1111/j.1745-9125.2008.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Self‐control, Routine Activities, and Fraud Victimization*

Abstract: Recent research has used both routine activity/lifestyle frameworks and self‐control theory to explain victimization. Thus far, combined tests of these theories have focused on offending populations and street crime victimization. Whether these frameworks also explain exposure to and likelihood of nonviolent victimization (e.g., fraud) in general‐population samples remains an open empirical question. Building on prior work, we assess the independent effects of routine consumer activities (i.e., remote purchasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
240
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(252 citation statements)
references
References 95 publications
10
240
1
1
Order By: Relevance
“…Van Wilsem (2013) found that low self-control was positively related to hacking victimization, while Bossler and Holt (2010) found that low self-control was neither related to hacking nor to malware victimization. However, Holtfreter, Reisig, and Pratt (2008) found that although targeting is random, the personal characteristics and behavior of the victim influenced who responded to a scam. As a result, low self-control may play a role in the risk of victimization regardless of the targeted nature of victimization.…”
Section: Assessing the Theoretical Explanations For The Victim-offendmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Wilsem (2013) found that low self-control was positively related to hacking victimization, while Bossler and Holt (2010) found that low self-control was neither related to hacking nor to malware victimization. However, Holtfreter, Reisig, and Pratt (2008) found that although targeting is random, the personal characteristics and behavior of the victim influenced who responded to a scam. As a result, low self-control may play a role in the risk of victimization regardless of the targeted nature of victimization.…”
Section: Assessing the Theoretical Explanations For The Victim-offendmentioning
confidence: 99%
“…The absence of measures may lead to model misspecification as online activity could increase the risk of offline crimes like fraud (Holtfreter, Reisig, and Pratt 2008). At the same time, traditional crimes might decrease because individuals spend more time online (Tcherni et al 2016).…”
Section: Routine Activities Theorymentioning
confidence: 99%
“…12 Kristy Holtfreter and her colleagues looked broadly at consumer fraud victimization and found that victims were more likely to have low self-control. 14 In contrast, it's been found that those who are considered sensation seekers aren't more likely to be scammed by the online dating romance scam; rather, for those who score high on the Romantic Belief Scale, idealization is more associated with the likelihood of being a victim. 7,11 In explaining the success of mass-marketing fraud, scholars mostly draw from social psychological theories and apply them to these scams.…”
Section: Vulnerability and Persuasive Techniquesmentioning
confidence: 88%
“…Studies on fraud victimization in the past have also tried to gain more insight in the sociodemographic characteristics of victims (Holtfreter et al, 2008;Sheng et al, 2010;Titus et al, 1995). It soon became clear however, that creating demographic profiles for fraud victims is a complex undertaking (Holtfreter et al, 2008).…”
Section: Characteristics Of the Phishing Targetmentioning
confidence: 99%